PENERAPAN ANIMASI 2D DAN 3D PADA GAME PROJECT SEKAI COLORFUL STAGE! FEAT. HATSUNE MIKU - Suci, Delyana (Anima Rupa, 2025)
Currently, animation has developed very rapidly. With the development of technology, various types of animation can be used in the game industry. This study discusses the use of 2D animation and 3D animation in the game “Project Sekai Colorful Stage! feat. Hatsune Miku”, which is a rhythm/music game that incorporates famous virtual characters from vocaloid especially Hatsune Miku. This research uses a descriptive qualitative method where I will conduct research by observing the animation used in this game. The game combines attractive visual elements and interactive gameplay, making it highly desirable to music and anime fans. 2D animation is used for the backgrounds and characters, giving it a cheerful and distinctive feel, while 3D animation gives depth and realism to the game environment. This game not only offers stunning visuals, but also enhances player interaction with the songs and characters through the incorporation of these two animation techniques. This research focuses on how the two techniques are combined and their effect on the game experience.